Unraveling the role of gut microbiota by fecal microbiota transplantation in rat model of kidney stone disease - Hunthai, Sittiphong; Usawachintachit, Manint; Taweevisit, Mana; Srisa-Art, Monpichar; Anegkamol, Weerapat; Tosukhowong, Piyaratana; Rattanachaisit, Pakkapon; Chuaypen, Natthaya; Dissayabutra, Thasinas (Scientific reports, 2024)
Emerging research on the microbiome highlights the significant role of gut health in the development of kidney stones, indicating that an imbalance in gut bacteria or dysbiosis can influence the formation of stones by altering oxalate metabolism and urinary metabolite profiles. In particular, the overabundance of specific bacteria such as Enterococcus and Oxalobacter spp., which are known to affect oxalate absorption, is observed in patients with urolithiasis. This study investigates the effects of gut dysbiosis on urolithiasis through fecal microbiota transplantation (FMT) from patients to rats and its impact on urinary mineral excretion and stone formation. Fecal samples from eight patients with calcium oxalate stones and ten healthy volunteers were collected to assess the gut microbiome. These samples were then transplanted to antibiotic-pretreated Wistar rats for a duration of four weeks. After transplantation, we evaluated changes in the fecal gut microbiome profile, urinary mineral excretion rates, and expression levels of intestinal zonula occluden-1 (ZO-1) , SLC26A6 and renal NF-κB . In humans, patients with urolithiasis exhibited increased urinary calcium and oxalate levels, along with decreased citrate excretion and increased urinary supersaturation index. The fecal microbiota showed a notable abundance of Bacteroidota . In rodents, urolithiasis-FMT rats showed urinary disturbances similar to patients, including elevated pH, oxalate level, and supersaturation index, despite negative renal pathology. In addition, a slight elevation in the expression of renal NF-κB , a significant intestinal SLC26A6 , and a reduction in ZO-1 expression were observed. The gut microbiome of urolithiasis-FMT rats showed an increased abundance of Bacteroidota , particularly Muribaculaceae , compared to their healthy FMT counterparts. In conclusion, the consistent overabundance of Bacteroidota in both urolithiasis patients and urolithiasis-FMT rats is related to altered intestinal barrier function, hyperoxaluria, and renal inflammation. These findings suggest that gut dysbiosis, characterized by an overgrowth of Bacteroidota , plays a crucial role in the pathogenesis of calcium oxalate urolithiasis, underscoring the potential of targeting the gut microbiota as a therapeutic strategy.